Exploring current hypervirulent Klebsiella pneumoniae infections: insights into pathogenesis, drug resistance, and vaccine prospects - Wang, Qingjing; Yu, Haojie; Pan, Xueer; Huang, Weichang; Lalsiamthara, Jonathan; Ullah, Saif; Xu, Yongchang; Lu, Anwei (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is a significant pathogenic bacterium responsible for a range of infections. The escalating prominence of K. pneumoniae in hospital-acquired infections is a deeply alarming trend that demands immediate attention and rigorous intervention. This article provides an up-to-date review of K. pneumoniae’s virulence factors, pathogenesis, and the mechanism driving drug resistance. It also explores the potential for safe and effective vaccine developments, vital for preventing and controlling these diseases. Furthermore, we summarize the epidemiological characteristics of classical and hypervirulent K. pneumoniae infections, providing an overview of drug-resistance K. pneumoniae emergence, transmission, and prevalence.